Conversion of carbazole carboxamide based reversible inhibitors of Bruton's tyrosine kinase (BTK) into potent, selective irreversible inhibitors in the carbazole, tetrahydrocarbazole, and a new 2, 3-dimethylindole series. Issue 18 (1st October 2018) - Liu, Qingjie; Batt, Douglas G.; Chaudhry, Charu; Lippy, Jonathan S.; Pattoli, Mark A.; Surti, Neha; Xu, Songmei; Carter, Percy H.; Burke, James R.; Tino, Joseph A.
Graphical abstract: Highlights: Electrophilic groups increased potency and selectivity of carbazole BTK inhibitors. Related indole analogs retained this potency and further increased selectivity. Irreversible inhibition was demonstrated using a dialysis assay. Better physicochemical characteristics accompanied the improved biochemical profile. Abstract: Incorporation of a suitably-placed electrophilic group transformed a series of reversible BTK inhibitors based on carbazole-1-carboxamide and tetrahydrocarbazole-1-carboxamide into potent, irreversible inhibitors. Removal of one ring from the core of these compounds provided a potent irreversible series of 2, 3-dimethylindole-7-carboxamides having excellent potency and improved selectivity, with the additional advantages of reduced lipophilicity and molecular weight.